Application of Cooperative Learning Model for Mathematics in Elementary School - Lailatun Nurul Hajar (Indonesian Journal of Applied Research (IJAR), 2020)
n the process of teaching and learning it will be fun if students have self-efficacy and the teacher has high creativity in teaching. The purpose of this study is to find out how much the relationship between teacher teaching creativity and self-efficacy of fifth grade students at SDN Sukamaju 03 District Cigudeg, Bogor Regency. This type of quantitative research is a functional relationship between variable X with variable Y, the subjects in this study were 1 group teacher that was sampled only grade V teachers who numbered 20 and class V students of SDN Sukamaju 03 totaling 20 students and the data obtained from questionnaires, Data collection techniques by questionnaire, observation, interview and documentation. Based on the results of testing using product moment, the correlation between teacher teaching creativity (X) with student self-efficacy (Y) obtained a value of rcount = 0.790 and rtable for 20 is 0.444 at level significance of 5% thus rcount > rtable (0.790> 0.444) then H0 is rejected, which means there is a significant correlation between creativity teaching self-efficacy of teachers with students. The significance of the regression equation obtained the Fcount of 29.840 and the Ftable of 4.41 with a sig value of 0.000, so that Fcount > Ftable, then there is a significant relationship between teacher teaching creativity (Variable X) and student self-efficacy (Variable Y). And this research is to get R2 = 0.624 62.4% showed their creativity variables affect self-efficacy of teachers to teach students, the remaining 37.6% influenced by other factors not an analysis in this study.